Structural regulation of myocytes in engineered healthy and diseased cardiac models - Yu, Jing (2021)
The development of cardiac models that faithfully recapitulate heart conditions is the goal of cardiac biomedical research. Among the numerous limitations of current models, replication of the cardiac microenvironment is one of the key challenges, and the effect of mechanical cues remains obscure in cardiac tissue. In this paper, different topological structures in the engineered cardiac models are summarized, and mechanical regulation of myocyte morphology and functional responses are discussed. Microenvironmental cues in vivo are influencing cardiac functions from cellular to tissue levels, and replications of these micro and macro features in the in vitro cardiac model shed light on cardiac research from a mechanistic point of view. With simple manipulation of topology, both physiological and pathological cardiac constructs can be remodeled to investigate the origin of abnormal cell phenotypes and functional responses in cardiac diseases. The integration of topological guidance with heart-on-a-chip devices is covered briefly and limitations of the current cardiac constructs are also addressed for future advancements in personalized medicine.